Analisis Framing terhadap Citra Gemoy dalam Portal Berita Online - Handayani, Hanifah (Multiverse: Open Multidisciplinary Journal, 2024)
This research aims to analyze how Kompas.com, Tribunnews.com, and CNNIndonesia.com frame news about the "gemoy" image of public figures. The researcher employed a descriptive and qualitative methodology, utilizing the Zhongdang Pan and Gerald M. Kosicki model to classify framing elements: syntactic, script, thematic, and rhetorical. The findings reveal that each online news portal has its own distinctive characteristics in framing the news: (1) Kompas.com tends to positively assess the "gemoy" image as an authentic reflection of the related figure; (2) Tribunnews.com is more critical and views "Politik Gemoy" as a campaign strategy that undermines democracy; (3) CNNIndonesia.com employs satire when addressing the "gemoy" image. This study highlights the diverse strategies used by media outlets to influence public perception and underscores the media's significant role in shaping political discourse. In conclusion, the media play a pivotal role in shaping public perception through the various framing approaches they employ.